Mammographic image quality in relation to positioning of the breast: A multicentre international evaluation of the assessment systems currently used, to provide an evidence base for establishing a standardised method of assessment. Issue 4 (November 2017) - Taylor, K.; Parashar, D.; Bouverat, G.; Poulos, A.; Gullien, R.; Stewart, E.; Aarre, R.; Crystal, P.; Wallis, M.
Abstract: Introduction: Optimum mammography positioning technique is necessary to maximise cancer detection. Current criteria for mammography appraisal lack reliability and validity with a need to develop a more objective system. We aimed to establish current international practice in assessing image quality (IQ), of screening mammograms then develop and validate a reproducible assessment tool. Methods: A questionnaire sent to centres in countries undertaking population screening identified practice, participants for an expert panel (EP) of radiologists/radiographers and a testing panel (TP) of radiographers. The EP developed category criteria and descriptors using a modified Delphi process to agree definitions. The EP scored 12 screening mammograms to test agreement then a main set of 178 cases. Weighted scores were derived for each descriptor enabling calculation of numerical parameters for each new category. The TP then scored the main set. Statistical analysis included ANOVA, t-tests and Kendall's coefficient. Results: 11 centres in 8 countries responded forming an EP of 7 members and TP of 44 members. The EP showed moderate agreement when the scoring the mini test set W = 0.50 p < 0.001 and the main set W = 0.55 p < 0.001, 'posterior nipple line' being the most difficult descriptor. The weighted total scores differentiated the 4 new categories Perfect, Good, Adequate and Inadequate (p < 0.001). Conclusion: We have developed an assessment tool by Delphi consensus and weighted consensus criteria. We have successfully tabulated a range of numerical scores for each new category providing the first validated and reproducible mammography IQ scoring system. Highlights: Establish current international practice in assessing image quality of screening mammograms. Develop and validate a new assessment tool. Weighted consensus list of criteria. Potentially the closest evidence to date of a quantitative assessment.